Kekuatan Hukum Sertifikat Tanah Elektronik dalam Menjamin Kepastian Hukum dan Perlindungan Pihak Ketiga - Devita Candra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The digital transformation in Indonesia's land sector is marked by the implementation of electronic land certificates as regulated under Minister of Agrarian Affairs and Spatial Planning/National Land Agency Regulation No. 1 of 2021. This policy aims to enhance efficiency and legal certainty in land administration. However, its implementation raises questions regarding the legal strength of electronic certificates and the protection of third parties, particularly good faith purchasers. This study uses a normative juridical approach to analyze the legal standing of electronic land certificates and the legal protection mechanisms for third parties in land transactions. The findings show that although electronic certificates hold the same legal force as physical certificates, there are still challenges related to data integration and legal safeguards for third parties. Strengthening regulations and the role of notaries/land deed officials (PPAT) is necessary to ensure the validity and legitimacy of electronic certificates and to achieve optimal legal certainty.